Evaluation of the impact of penile anomalous anatomy on the surgical management of hypospadias in Gezira National Centre for Paediatrics Surgery (Global Journal of Medical Research, 2013)
Introduction: The fact that there are over 250 methods of surgical correction of hypospadias described in the literature indicates that the â€œhypospadiologistsâ€ are still in search of the ideal technique for repair. Objectives: To evaluate the impact of penile anatomy on the surgical management of hypospadias. Results: Fourty four patients with different types of hypospadias 88.6% presented more than one year and 11.4% less .we found that 11.4% had glandular meatus,43.2% distal and 45.4% proximal ,also 43.2% had no chordee,45.4% had superficial and 11.4% deep chordee, meatal site after chordee correction24% distal , 60 % proximal and 16% penoscrotal.
Keywords: penile hypospadias; penile anomalous; surgical repair; outcome